Transfer of Ideological Stances through Stylistic Choices in Translation: The Case of the Persian Subtitle of The Matrix - Sima Imani; Jalil Jalali (Media and Intercultural Communication: A Multidisciplinary Journal)
Although a great deal has been written on the technical and linguistic aspects of subtitling, less attention has been paid to the stylistic analysis of subtitles. Nevertheless, stylistic choices of the subtitler could reveal the ideologies of the translator and filmmakers. Subtitling in Iran is mainly performed by fans, and their subtitles are widely used on various unauthorized websites. Since they translate out of passion and remain unpaid for what they do, unlike in official dubbing, there is little ideological and institutional pressures on the translator’s choices. In the present study, the Persian subtitle of the film (The Matrix, 1999) was selected as the case study. The study aimed to investigate how the subtitler presents his unique style of subtitling and, by so doing, reveals the ideology of the film as well. The results showed the use of various stylistic strategies, namely the explication of dialogues, the expansion of acronyms, the addition of information, and the explanation of allusions.